Quality audit moderates the influence of good governance on company value - Dina Nurhasanah; Sugi Suhartono (Jurnal Ekonomi Perusahaan, 2022)
The mechanisms and principles of good corporate governance are crucial to increasing company value. However, this principle is still missed by many companies. Qualified auditors that can conduct a good auditing quality are the key to this issue. This research departs from a belief that the ability of audit quality moderates the effect of good corporate governance on company value. This study aims to confirm this notion. Therefore, the authors analyze the data from 129 companies taken purposively from various industries listed on the Indonesia Stock Exchange from 2017 to 2019, using the pooling test as the primary analysis tool. This study reveals that institutional ownership positively influences company value. As expected, audit quality moderates this relationship. However, this study fails to confirm the effect of the board of commissioners and managerial ownership on company value. Moreover, audit quality also fails to show its moderating effect in those unconfirmed relationships. The authors propose suggestions for further research. Original Article | Turnitin